2009
DOI: 10.1073/pnas.0906979106
|View full text |Cite
|
Sign up to set email alerts
|

Real-time observation of the transition from transcription initiation to elongation of the RNA polymerase

Abstract: The transition from initiation to elongation of the RNA polymerase (RNAP) is an important stage of transcription that often limits the production of the full-length RNA. Little is known about the RNAP transition kinetics and the steps that dictate the transition rate, because of the challenge in monitoring subpopulations of the transient and heterogeneous transcribing complexes in rapid and real time. Here, we have dissected the complete transcription initiation pathway of T7 RNAP by using kinetic modeling of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(100 citation statements)
references
References 45 publications
5
91
4
Order By: Relevance
“…The halt position-dependent profiles reveal that the wild type enzyme begins transitioning to elongation at about position ϩ8. This behavior is consistent with recent single molecule measurements that show a very slow transition to elongation commencing at position ϩ8, and increasing for complexes halted at positions ϩ9 and ϩ10 (20). Importantly, these data show that the P266L mutant is not transitioning to elongation significantly at position ϩ9, but instead the onset of its transition is delayed to about position ϩ11.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The halt position-dependent profiles reveal that the wild type enzyme begins transitioning to elongation at about position ϩ8. This behavior is consistent with recent single molecule measurements that show a very slow transition to elongation commencing at position ϩ8, and increasing for complexes halted at positions ϩ9 and ϩ10 (20). Importantly, these data show that the P266L mutant is not transitioning to elongation significantly at position ϩ9, but instead the onset of its transition is delayed to about position ϩ11.…”
Section: Discussionsupporting
confidence: 80%
“…Fluorescence does not return to the fully free DNA base line. Halting at positions ϩ10 and beyond yields a more complete transition, indicating faster rates of transition to elongation, as seen previously (20).…”
Section: Resultssupporting
confidence: 61%
“…Ha and coworkers showed that it is possible to perform FRET investigations with single-molecule sensitivity, [4] which has led to the wide spread use of single-pair FRET (spFRET) to investigate intra-and intermolecular distances and thereby conformations and dynamics in order to provide new insights into a number of biological questions. [5][6][7][8][9][10][11][12][13][14][15][16][17] SpFRET measurements can be performed either on immobilized molecules or on molecules in solution using a burst analysis. [18] In the solution-based experiments, the fluorescence of a dilute (of the order of 20-50 pm) solution of labeled molecules coming from the~fL volume of the focus of a confocal microscope is measured using a high numerical aperture objective.…”
Section: Introductionmentioning
confidence: 99%
“…Intricate interactions between RNA polymerase II and its chromatin environment are essential for proper transcription progression through initiation, elongation, and termination (64,65). Although chromatin remodeling has been widely investigated in ER␣-regulated transcription, and various histone-modifying factors, including histone acetyltransferases p300/CBP and GCN5/pCAF (15,22) and histone methyltransferases CARM1, PRMT1, G9a, RIZ1, NSD1, MLL2, and SMYD3 have been implicated in this process, how histone modifications dictate ER␣-regulated transcription is still not fully understood.…”
Section: Discussionmentioning
confidence: 99%